The new (Version 9) American Joint Committee on Cancer tumor, node, metastasis staging for cervical cancer. (30th March 2021) - Olawaiye, Alexander B.; Baker, Thomas P.; Washington, M. Kay; Mutch, David G.
Abstract: The American Joint Committee on Cancer (AJCC) tumor, node, metastasis (TNM) staging for all cancer sites has been periodically updated as a published manual for many years. The last update, the eighth edition AJCC Cancer Staging Manual went into use on January 1, 2018. The AJCC has since restructured and updated its processes, and all AJCC staging‐related data are now housed on its new application programming interface. Consequently, the next AJCC TNM staging update, AJCC version 9 TNM staging, will be published electronically and will be released chapter by chapter. The first chapter of version 9 AJCC TNM staging is the updated cervical cancer staging, which is now published. This article highlights the changes to the AJCC TNM cervical cancer staging; these changes align with the International Federation of Gynecology and Obstetrics staging. The most important of the changes are: 1) the incorporation of imaging and surgical findings, 2) the elimination of lateral spread from T1a, 3) the addition of a subcategory to T1b (T1b3), and 4) histopathology is updated to reflect human papillomavirus‐associated and human papillomavirus‐independent carcinomas.